Manufacturing of Cutting Saw Machine for Aluminum - Anhar Khalid; Akbar Ela Heka (International Journal of Integrated Science and Technology, 2024)
Aluminum is a metal material that is widely used in various industrial sectors, such as automotive and construction, because of its lightweight and corrosion-resistant properties. However, aluminum cutting often faces technical challenges, such as overheating that can affect the quality of the piece. The research aims to design and build a prototype of a cutting saw machine specifically designed for aluminum materials, with a focus on efficiency, low cost, and ergonomics. The research uses an engineering experiment approach with the stages of CAD-assisted design, component manufacturing, and performance testing. Prototypes are tested to evaluate cutting speed, operational stability, and energy efficiency. The results show that the machine is able to cut aluminum at a speed of 86.13 mm/min, high energy efficiency, and adequate stability. This study fills the gap of previous research that focused more on heavy metal cutting machines, such as steel. These findings make a significant contribution to aluminum processing technology, especially for small and medium-sized industries. This study recommends the development of automation systems and the use of alternative materials to improve engine performance.